Analysis of the Relationship Between Maternal Age, Parity, and Maternal Occupation and the Incidence of Low Birth Weight (LBW) at Tanon II Community Health Center, Sragen Regency, in 2025 - Muflihatun Indriyani Permatasari (Indonesian Journal of Innovation Science and Knowledge, 2026)
it increases the risk of neonatal morbidity and mortality. This study aimed to analyze the association of maternal age, parity, and maternal occupation with LBW at Tanon II Community Health Center, Sragen Regency, in 2025. A quantitative analytical observational study with a case-control design was conducted using 2025 delivery medical records. The sample consisted of 48 respondents: 24 LBW cases and 24 controls. Data were analyzed using the Chi-Square test and multiple logistic regression. Bivariate analysis showed significant associations between maternal age (p=0.000; OR=12.143), parity (p=0.000; OR=14.000), maternal occupation (p=0.009; OR=4.857), and LBW. Multivariate analysis showed that maternal age (AOR=9.140; p=0.011) and parity (AOR=6.588; p=0.032) remained significant, whereas maternal occupation was not significant (AOR=4.748; p=0.063). Maternal age was the most dominant factor. These findings support strengthening high-risk pregnancy screening, antenatal care, and reproductive health education at the primary health-care level.